2021
DOI: 10.1186/s12894-021-00807-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing the cytotoxic action of Docetaxel induced by Pentoxifylline in a PC3 prostate cancer cell line

Abstract: Background Prostate cancer is one of the most frequently diagnosed types of cancers worldwide. In its initial period, the tumor is hormone-sensitive, but in advanced states, it evolves into a metastatic castration-resistant tumor. In this state, chemotherapy with taxanes such as Docetaxel (DTX) comprises the first line of treatment. However, the response is poor due to chemoresistance and toxicity. On the other hand, Pentoxifylline (PTX) is an unspecific inhibitor of phosphodiesterases; experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Our recent work discovered that pentoxifylline, an anti-fibrotic drug approved for the treatment of vascular diseases [ 15 , 16 ] , increased the response of pancreatic cancer cells to gemcitabine treatment [ 17 ] . The chemosensitizing effect of pentoxifylline has also been described in cervical [ 18 , 19 ] , prostate [ 20 ] , and human pancreatic tumor xenografts [ 21 ] . In NSCLC cells, Ohsaki et al reported the benefit of combining pentoxifylline with cisplatin and etoposide by interfering with the cell cycle [ 22 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work discovered that pentoxifylline, an anti-fibrotic drug approved for the treatment of vascular diseases [ 15 , 16 ] , increased the response of pancreatic cancer cells to gemcitabine treatment [ 17 ] . The chemosensitizing effect of pentoxifylline has also been described in cervical [ 18 , 19 ] , prostate [ 20 ] , and human pancreatic tumor xenografts [ 21 ] . In NSCLC cells, Ohsaki et al reported the benefit of combining pentoxifylline with cisplatin and etoposide by interfering with the cell cycle [ 22 ] .…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer in vitro, inhibition of a kappa-lightchain-enhancer of activated B-cells (NF-kB) by pentoxifylline enhances docetaxel-induced apoptosis, and pentoxifylline alone has also been found to possess antitumor activity comparable to that of docetaxel 5 . The use of this hemorheology in clinical studies has yielded good results.…”
mentioning
confidence: 99%